Application of Computational Fluid Dynamics Simulation in The Case of Upward Vertical Core Annular Flow of Oil-Water System - Dianita, Cindy; Nur Fatimah, Rana; Wahid, Abdul (Testing Center for Oil and Gas LEMIGAS, 2026)
The energy required to transport heavy oil through pipelines can be significantly lowered by applying the core-annular flow (CAF) technique, in which a layer of water surrounds the oil as it moves through the pipe. This research investigates the behavior of upward oil–water flow in vertical pipelines using three-dimensional computational fluid dynamics (CFD) simulations. The numerical analysis is conducted based on previously published experimental studies. Validation has been completed to ensure the visual and numerical consistency of the observed interfacial wave geometry. This CFD work captures the wavy bamboo CAF pattern, illustrating the effect of buoyancy and pressure gradient in upward vertical flow, as demonstrated by experimental results. The present CFD simulation results indicate a relatively stable velocity distribution, where the central region of the pipe contains the highest concentration of oil. In addition, the absolute pressure gradually decreases along the length of the pipe, while the wall shear stress remains relatively low. The influence of gravity affecting the flow is investigated, showing a higher pressure drop compared to gravity-free flow. Compared with single-phase heavy oil transport, the CAF technique demonstrates significantly higher efficiency, achieving energy savings exceeding 90%. Furthermore, the three-dimensional simulation developed in this study provides more detailed flow pattern representation and more reliable hydrodynamic predictions than those obtained from earlier two-dimensional analyses.